Cognitive Biases, Social Influence, and Emotion in Recruitment Decisions: Evidence from Young HR Managers - Zaeni, Nurhaeda; Maryadi, Maryadi; S., M. Salim; Kitta, Syafruddin; Baharuddin, Andi Harnas (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Recruitment decisions are rarely the outcome of purely rational judgment; they are shaped by social pressures, emotional reactions, and cognitive distortions. By examining these dynamics, this study adds precision to our understanding of how decision-making unfolds within human resource management. Drawing on survey data from 401 young HR managers in Indonesia and analyzed using partial least squares structural equation modeling (PLS-SEM), the study investigates the influence of cognitive bias and social influence on recruitment decisions, with emotion as a mediator. The findings reveal that cognitive bias does not directly determine recruitment outcomes but shapes emotion, which in turn has a modest effect. Social influence emerges as the dominant driver, exerting both direct and emotion-mediated effects on decisions. These results demonstrate that recruitment is a socially embedded and emotionally mediated process. For managers, the implication is clear: recruitment systems must regulate social pressures and emotional spillovers to ensure fairness and effectiveness.